Developments in Generative Learning using a Collaborative Learning Environment - Joyes, Gordon; Fisher, Tony; Coyle, Do (Proceedings of the International Conference on Networked Learning, 2002)
This paper describes and reflects upon the development of the on-line modules for the EdD in Teacher Education at the University of Nottingham, UK. This development has provided the course organisers with an opportunity to explore on-line collaborative learning involving knowledge transformation and creation. The course attracts mainly overseas students and consists of four taught modules followed by an equivalent period of research leading to a thesis. The paper presents the rationale for the pedagogic approach taken in developing the course including the rationale for the use of WebQuests and a collaborative learning environment (CLE) that is being developed by the University of Melbourne, Australia.